The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2478/orga-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Citizenship Behavior: A Mediating Effect of Organizational Commitment

Abstract: Background and Purpose: Recently, job satisfaction has become a center of attention among academics, behavioral scientists, and business practitioners. Drawing on the tenet of the social exchange theory (SET) perspective and extending the conceptualization of the same, the present study aims at investigating the relationships among job satisfaction, organizational commitment, and citizenship behavior and mediation mechanism to unearth the effect of job satisfaction and organizational commitment on citizenship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
(96 reference statements)
1
4
0
1
Order By: Relevance
“…This finding demonstrates the existence of the discriminant validity of the scales. Moreover, from table 1, it is found that the factor loading is more than 0.70 for each construct that also confirms the discriminant validity of the scales (Haque et al 2019;Kline 2005).…”
Section: Measurement Modelsupporting
confidence: 63%
See 1 more Smart Citation
“…This finding demonstrates the existence of the discriminant validity of the scales. Moreover, from table 1, it is found that the factor loading is more than 0.70 for each construct that also confirms the discriminant validity of the scales (Haque et al 2019;Kline 2005).…”
Section: Measurement Modelsupporting
confidence: 63%
“…Committed and proactive employees can ensure the competitiveness of the organizations (Yen and Teng 2013). The development of favorable working environments is essential for creating committed teams and their performance (Haque, et al 2019). SL has a positive influence on both organizational commitment (OC) (Bobbio, Dierendonck, and Manganelli 2012;Van Dierendonck and Nuijten 2011;Zhou and Miao 2014) and organizational citizenship behavior (OCB) (Abid, Gulzar, and Hussain 2015;Bobbio et al 2012;Yang and Min 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction is an indicator in producing maximum work behavior (Ni et al, 2020;Tafzal Haque et al, 2019). It comes from what an organization has given its members.…”
Section: The Effect Of Job Satisfaction On Organizational Citizenship Behaviormentioning
confidence: 99%
“…The specific fit indexes included χ 2 = 607.70, df = 203, χ 2 / df = 2.994 < 3.00, RMSEA = 0.074 < 0.800, CFI = 0.920 > 0.900, TLI = 0.909 > 0.900, and SRMR = 0.068 < 0.800 (Fan et al, 2019; Ucar et al, 2021). Then, we used Composite Reliability (CR) and Average Variance Extracted (AVE) to further test the measurement model (Haque et al, 2019; Jyoti & Bhau, 2015). The results showed that the CR values for four constructs were respectively 0.949, 0.889, 0.895, 0.956, which all exceeded the required threshold values of 0.70, and the AVE values for four constructs were respectively 0.861, 0.619, 0.588, 0.687, all exceeding the required threshold values of 0.50, too.…”
Section: Resultsmentioning
confidence: 99%